Genome comparison between clinical and environmental strains of Herbaspirillum seropedicae reveals a potential new emerging bacterium adapted to human hosts - Faoro, Helisson (BMC Genomics, 2019)
BACKGROUND: Herbaspirillum seropedicae is an environmental β-proteobacterium that is capable of promoting the growth of economically relevant plants through biological nitrogen fixation and phytohormone production. However, strains of H. seropedicae have been isolated from immunocompromised patients and associated with human infections and deaths. In this work, we sequenced the genomes of two clinical strains of H. seropedicae, AU14040 and AU13965, and compared them with the genomes of strains described as having an environmental origin. RESULTS: Both genomes were closed, indicating a single circular chromosome; however, strain AU13965 also carried a plasmid of 42,977 bp, the first described in the genus Herbaspirillum. Genome comparison revealed that the clinical strains lost the gene sets related to biological nitrogen fixation (nif) and the type 3 secretion system (T3SS), which has been described to be essential for interactions with plants. Comparison of the pan-genomes of clinical and environmental strains revealed different sets of accessorial genes. However, antimicrobial resistance genes were found in the same proportion in all analyzed genomes. The clinical strains also acquired new genes and genomic islands that may be related to host interactions. Among the acquired islands was a cluster of genes related to lipopolysaccharide (LPS) biosynthesis. Although highly conserved in environmental strains, the LPS biosynthesis genes in the two clinical strains presented unique and non-orthologous genes within the genus Herbaspirillum. Furthermore, the AU14040 strain cluster contained the neuABC genes, which are responsible for sialic acid (Neu5Ac) biosynthesis, indicating that this bacterium could add it to its lipopolysaccharide. The Neu5Ac-linked LPS could increase the bacterial resilience in the host aiding in the evasion of the immune system. CONCLUSIONS: Our findings suggest that the lifestyle transition from environment to opportunist led to the loss and acquisition of specific genes allowing adaptations to colonize and survive in new hosts. It is possible that these substitutions may be the starting point for interactions with new hosts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5982-9) contains supplementary material, which is available to authorized users.